1982
DOI: 10.1044/jshd.4701.43
|View full text |Cite
|
Sign up to set email alerts
|

Gesture Recognition in Patients with Aphasia

Abstract: This study focuses on the controversial issue of the integrity of gestural communication abilities in subjects with aphasia. To define the ability of subjects to interpret symbolic gestures, an Amer-Ind Recognition Test (ART) was developed which required no verbal response from the examiner or the subject. The relationships between impairment of Amer-Ind signal recognition and (a) severity of aphasia, (b) listening and talking abilities and (c) the type of response picture used were investigated. Whether subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Neuropsychological studies on patients with frontal aphasia patients have shown deficits in several aspects of the motor domain, in line with the role that Broca's area plays in such mechanisms. Supralinguistic impairments were described that affected such nonverbal abilities as recognizing signs, gestures, and pantomimes 43,44 . Tranel and colleagues demonstrated that left frontal brain‐damaged patients have difficulties in understanding details of action when presented with cards depicting various actions 45 .…”
Section: Broca's Area In Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropsychological studies on patients with frontal aphasia patients have shown deficits in several aspects of the motor domain, in line with the role that Broca's area plays in such mechanisms. Supralinguistic impairments were described that affected such nonverbal abilities as recognizing signs, gestures, and pantomimes 43,44 . Tranel and colleagues demonstrated that left frontal brain‐damaged patients have difficulties in understanding details of action when presented with cards depicting various actions 45 .…”
Section: Broca's Area In Actionmentioning
confidence: 99%
“…Supralinguistic impairments were described that affected such nonverbal abilities as recognizing signs, gestures, and pantomimes. 43,44 Tranel and colleagues demonstrated that left frontal brain-damaged patients have difficulties in understanding details of action when presented with cards depicting various actions. 45 Furthermore, it has been demonstrated that patients with aphasia show a correlation be-tween action comprehension (through pantomime interpretation) and reading comprehension deficits.…”
Section: Broca's Area In Actionmentioning
confidence: 99%
“…Tasks usually involve the standard usage of an object being gestured and an individual indicates the object that the gesture refers to (Duffy and Duffy 1981, Daniloff et al 1982, 1986, Varney 1982, Lambier and Bradley 1991, Thorburn et al 1995). The findings of these studies have indicated that impaired comprehension of pantomime is unrelated to severity of aphasia (Daniloff et al 1982). It has, however, been found to be more frequent in participants with posterior lesions than participants with anterior lesions (Varney 1982, Daniloff et al 1986, Lambier and Bradley 1991).…”
Section: Introductionmentioning
confidence: 99%
“…These nonverbal skills may not require verbal mediation. Daniloff et al (1982) found that aphasic patients were able to recognize iconic gestural systems (Amerind) leading to the authors to conclude that the aphasia exhibited in their subjects was a disorder specific to the linguistic system rather than a general representational disorder. study, subjects were asked to comment on twenty topics while they were videotaped.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have examined the gestural abilities of aphasic patients (Cicone, Wapner, Foldi, Zurif & Gardner, 19797 Duffy & Duffy, 19817 Peterson & Kirshner, 1981;Feyereisen & Seron, 1982;Daniloff, Noll, Fristoe & Lloyd, 1982;and Behrmann & Penn, 1985). The focus of this work has been a determination of whether or not patients with aphasia, a language disorder, suffer from a corresponding disorder of their gestural abilities.…”
Section: Introductionmentioning
confidence: 99%